The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/cea.13193
|View full text |Cite
|
Sign up to set email alerts
|

Exploring what motivates and sustains support group engagement amongst young people with allergies: A qualitative study

Abstract: Participants valued the psychological and practical support of networking with others with allergies, and described how membership improved their confidence. This study also provides insight into the ways support groups improve young people's adherence to medical advice and positive self-care behaviours; participants responded well to hard-hitting video campaigns which appeared to emphasize the severity and susceptibility of anaphylaxis. Participants identified the need for more active promotion of support gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Illness comprehension by adolescents, particularly as they get older, may be an important target for intervention aimed at improving their psychological well‐being. Recently, Jones et al found that joining a support group improved self‐efficacy and confidence in allergy management in adolescents. The BIPQ can help identify adolescents showing psychological difficulties, with a particular focus on young women who seem to be more vulnerable, and guide clinicians to provide the right support for them.…”
Section: Discussionmentioning
confidence: 99%
“…Illness comprehension by adolescents, particularly as they get older, may be an important target for intervention aimed at improving their psychological well‐being. Recently, Jones et al found that joining a support group improved self‐efficacy and confidence in allergy management in adolescents. The BIPQ can help identify adolescents showing psychological difficulties, with a particular focus on young women who seem to be more vulnerable, and guide clinicians to provide the right support for them.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for healthcare professionals to be aware of the lack of understanding of the condition by patients, especially of the seriousness of the condition, the impact anaphylaxis has on psychological distress and the importance of social support from others. Jones et al have found that joining a support group improved self‐efficacy and confidence in allergy management in adolescents. Such support should be encouraged for adults with anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a limit to the support available from healthcare professionals. Jones et al explored what motivates young people with allergies to engage with support groups using in‐depth, semi‐structured interviews. They reported very positive findings with reported improved self‐esteem and confidence and improved adherence to self‐management behaviours.…”
Section: Clinical Allergymentioning
confidence: 99%